The Phenomenon of Research and Development Method in Research of Software Engineering - Mufadhol Mufadhol; Siswanto Siswanto; Djarot Dian Susatyono; Maya Utami Dewi (International Journal of Artificial Intelligence Research, 2017)
Progress of science and technology is very influential to development of software engineering. Communication between software developers and prospective users of software engineering by prototype system is very important in the development of software engineering. Research and Development method in research of software engineering is very suitable be used because supports the existence of such communications. But it is found there are several research that use this method with not perfect or not completed, so research results produced less fit with purpose. This paper will be explain how to used the stages must be carried out in research of software engineering with the method of research and development, in order to make the research more be effectively and efficiently as well as software development efforts that simultaneously accompanied by the validation effort for the results to be achieved in accordance with the expected goals.